Phylogenetic Relationship of Selected Species in the Family Muscicapidae inferred from Partial Mitochondria DNA Cytochrome Oxidase I Gene - Nur Jihan, Daud (Universiti Malaysia Sarawak (UNIMAS), 2008)
The phylogeny of Muscicapidae species (Passeriformes; Muscicapoidea) remains controversial. Phylogenetic relationships within this family were investigated based on analysis of mitochondria Cytochrome Oxidase I (COI) gene sequences. Nine species representing six putative Muscicapidae genera were successfully sequenced with 537 bp. Pycnonotus plumosus was selected as outgroup. Three different trees; Neighbour-joining (NJ), Maximum Parsimony (MP), and Maximum Likelihood (ML) were constructed using PAUP Program. The result shows that all phylogenetic trees produce different topology. Certain genera are unresolved, such as Philentoma and Rhipidura. However, these results resolve the phylogenetic relationship among some genera and species, and provide a molecular phylogenetic relationship among selected species in Muscicapidae.